2006
DOI: 10.1136/ard.2005.040832
|View full text |Cite
|
Sign up to set email alerts
|

An epistatic effect of the female specific loci on the development of autoimmune vasculitis and antinuclear autoantibody in murine lupus

Abstract: Objective: To identify the genetic loci regulating the incidence and severity of renal autoimmune vasculitis developed in murine lupus. Methods: Vasculitis of renal arteries was histopathologically evaluated in MRL/Mp-Fas lpr (MRL/lpr), C57BL/6-Fas lpr (B6/lpr), (MRL/lpr6B6/lpr) F 1 , and MRL/lpr6(MRL/lpr6B6/lpr) F 1 backcross mice. Using genomic DNA samples of the backcross mice, genome-wide scans, association studies, and linkage analyses were carried out based on genotypes of polymorphic microsatellite mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Previous studies have suggested the lack of SrD in MRL/lpr mice [22][23][24][25]. In the early stage of this study, we carefully confirmed that MRL/lpr mice hardly display any SrD related to the severity of autoimmune phenotypes, including glomerulonephritis (GN), splenomegaly (SpM), and autoantibody to nuclear antigens (ANA).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous studies have suggested the lack of SrD in MRL/lpr mice [22][23][24][25]. In the early stage of this study, we carefully confirmed that MRL/lpr mice hardly display any SrD related to the severity of autoimmune phenotypes, including glomerulonephritis (GN), splenomegaly (SpM), and autoantibody to nuclear antigens (ANA).…”
Section: Introductionsupporting
confidence: 81%
“…There are inconsistent facts that MBN2 mice show remarkable SrD in autoimmune phenotypes, while their ancestral MRL/lpr mice do not show significant SrD. Past studies have readily confirmed little SrD in the autoimmune phenotypes of an MRL/lpr strain [22][23][24][25]. Here, a question that arose was why the male-specific suppression by Marc4 had attenuated in the male mice of this strain.…”
Section: Discussionmentioning
confidence: 89%
“…In MRL-Fas lpr mice, the polymorphisms of Cd22, Fcgr2b, Spp1, IL10ra, and Coro1a were reported to be associated with autoimmune phenotypes (11,(38)(39)(40)(41). Of particular interest, the epistatic interaction between Cd72 and Fcgr2b in the development of autoimmune diseases has been observed in both humans and mice (42,43). The occurrence of polygenic diseases has been explained in a threshold-liability model, in which individuals develop the disease when the total number of disease-susceptibility genes exceeds a given threshold.…”
Section: Discussionmentioning
confidence: 99%
“…An MRL/lpr strain carries a loss‐of‐function mutation of Fas gene ( lpr ) which encodes an apoptosis receptor on lymphocytes [5]. The lpr mutation is necessary for the onset of autoimmune diseases in MRL/lpr; however, the other lpr ‐congenic strains, including C3H/He.Fas lpr (C3H/lpr), C57BL/6.Fas lpr and AKR.Fas lpr , barely develop autoimmune diseases [6–9]. The strain difference in the lpr constraint also influences the longevity of mice.…”
Section: Introductionmentioning
confidence: 99%